Literary Analysis: Chimamanda Adichie and Upton Sinclair's Narrative Strategies - Bharathan, Sujitha (Journal of Educational Research and Policies, 2025)
This article explores the thematic intersections between Upton Sinclair’s The Jungle and Chimamanda Ngozi Adichie’s Americanah. Despite their different eras and contexts, both authors address societal issues such as inequality, discrimination, and corruption. Through comparative analysis, this study examines their literary approaches and their impact on public consciousness and policymaking, highlighting their shared advocacy for social justice.